Implementation of Digital Promotion and Product Adaptation to Build Local Brands for Garut Leather Craft MSMEs - Sobar, Agus (International Journal of Science and Society, 2025)
This study aims to analyze the strategies of Garut leather craft SMEs in facing global competition challenges through Digital Promotion Strategies, Product Adaptation, and Local Brand Image Building. Although local products have high cultural value, business actors often face obstacles in the form of weak branding strategies and marketing that are not adaptive to international consumer preferences. The method used was quantitative with purposive sampling of 100 respondents, where the data was analyzed using Structural Equation Modelling (SEM) through SmartPLS. The results of the study show that digital promotion strategies and product adaptation have a positive and significant effect on strengthening Local Brand Image and Market Penetration Effectiveness. The use of social media and interactive content is effective in building trust, while design modifications that follow modern trends but still maintain authentic values are proven to strengthen brand identity. The main findings confirm that Local Brand Image acts as a crucial mediating variable, bridging the influence of promotion and product innovation on market success. This model demonstrates very high predictive power with an R-Square value of 0.968 for market penetration. In conclusion, the synergy between creative digital marketing and product development flexibility is the key for MSMEs to win the competition in the international market in a sustainable manner.